2022
DOI: 10.3390/su142013547
|View full text |Cite
|
Sign up to set email alerts
|

Societal Trust Related to COVID-19 Vaccination: Evidence from Western Balkans

Abstract: The lower rates of COVID-19 vaccination in Western Balkans countries could be partially explained by societal distrust of its citizens, jeopardizing the sustainability of COVID-19 vaccination programs. The aim of the study was to determine the level and predictors of societal trust in five countries of the region. Using an online questionnaire, data were obtained from 1157 respondents from Albania, Bosnia and Herzegovina, Montenegro, North Macedonia, and Serbia. The instrument included a socio-demographic ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
1
3
0
1
Order By: Relevance
“…Several factors emerging as relevant to vaccination attitudes in our study converge with other investigations of predictors of COVID-19 vaccination attitudes. For example, our finding of the significance of public health trust is consistent with the findings of Chen, Lee, and Lin [ 38 ], Cvjetkovic et al [ 39 ], and De Freitas, Basdeo, and Wang [ 40 ] about the positive impact of trust in the government, healthcare, and civil society on openness to COVID-19 vaccination. The importance of party affiliation is consistent with Khubchandani et al [ 67 ] and Agarwal et al [ 48 ] and the importance of information literacy with Engelbrecht, Kigozi, and Heunis [ 36 ] and Takahashi et al [ 8 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Several factors emerging as relevant to vaccination attitudes in our study converge with other investigations of predictors of COVID-19 vaccination attitudes. For example, our finding of the significance of public health trust is consistent with the findings of Chen, Lee, and Lin [ 38 ], Cvjetkovic et al [ 39 ], and De Freitas, Basdeo, and Wang [ 40 ] about the positive impact of trust in the government, healthcare, and civil society on openness to COVID-19 vaccination. The importance of party affiliation is consistent with Khubchandani et al [ 67 ] and Agarwal et al [ 48 ] and the importance of information literacy with Engelbrecht, Kigozi, and Heunis [ 36 ] and Takahashi et al [ 8 ].…”
Section: Discussionsupporting
confidence: 91%
“…In general, people differ in how much they trust others; interpersonal trust is higher in well-functioning communities and democratic societies [ 37 ]. Across the world, trust in the government, the healthcare system, and civil society correlates with COVID-19 vaccine acceptance and uptake [ 38 , 39 , 40 ]. In the US, studies have revealed that distrust of pharmaceutical companies, with them being perceived as being motivated by profit [ 41 ] and, overall, trust in the U.S. federal government have been waning since the Vietnam War era [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…It can potentially increase the mortality and morbidity from polio, measles, and other vaccine-preventable diseases, particularly in countries with low coverage ( Macdonald et al, 2020 ; Seyed et al, 2022 ). Some European countries and most of Balkan countries have a huge problem with vaccination coverage because of the misinformation about the safety of the vaccine and their efficacy, and that’s a problem that health organisation must know because the fear is the root of most problems ( Cvjetkovic et al, 2022 ; Fan et al, 2022 ). Immunization programs should be strengthened within primary healthcare ( Effraimidou et al, 2023 ) Countries should also implement robust surveillance systems to identify and close immunity gaps ( Blanc et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pandemi Covid-19 yang terjadi di seluruh dunia pada tahun 2020, tak terkecuali Indonesia. Indonesia, merupakan sebuah negara kepulauan yang terletak di Asia tenggara dengan luas 1,905 juta (Cvjetkovic et al, 2022). Dampak yang diakibatkan dari pandemi covid-19 dalam aspek Kesehatan, sosial ataupun ekonomi membuat Indonesia harus membuat kebijakan yang cepat dan tegas (Balut et al, 2022).…”
Section: Pendahuluanunclassified